Physicochemical Factors Affecting Microbiota Dynamics During Traditional Solid-State Fermentation of Chinese Strong-Flavor Baijiu - Guan, Tongwei; Lin, Yijin; Chen, Kebao; Ou, Mengying; Zhang, Jiaxu (Frontiers in Microbiology, 2020)
Spontaneous solid-state fermentation (SSF) of Chinese liquor was triggered and mediated to a large extent by microorganisms that colonize in the pit mud (PM). Given that the transfer of interphase microflora during the fermentation is a continuous and dynamic process, longitudinal studies are essential to provide ecological insights into community stability and response to consecutive disturbances in the process. In this context, this study aimed to generate a comprehensive longitudinal characterization of the microbiota during the fermentation processes of Chinese strong-flavor Baijiu (CSFB) differing in cellar ages with consideration for potential relation to physicochemical variables. The microecology variations observed during the 6-year cellar SSF (SCSSF) and 30-year cellars SSF (TCSSF) processes reveal that fungal composition contributes to a larger extent than bacterial composition to such variations. Orders of Lactobacillales, Anaerolineales, Enterobacteriales, Bacillales, Eurotiales and Saccharomycetales dominated (average relative abundances > 10%) the microbiota both in SCSSF and TCSSF processes but with a different percentage in the OTUs abundances. Compared with the SCSSF process, TCSSF possessed slower microbial succession rates, which were in accordance with the profile of physicochemical properties. From a network perspective, the microbial community structure observed in the TCSSF processes was more stable than that in the SCSSF. This may benefit from the milder physicochemical conditions of the TCSSF processes, especially the temperature, which is also more beneficial to the growth of some groups that have negative effects on fermentation, such as Staphylococcus, Pseudomonas and Acinetobacter.